Application-based covid-19 micro-mobility solution for safe and smart navigation in pandemics - Mishra, Sumit (2021)
Mishra, S., Singh, N., & Bhattacharya, D. (2021). Application-based covid-19 micro-mobility solution for safe and smart navigation in pandemics. ISPRS International Journal of Geo-Information, 10(8), 1-19. [571]. https://doi.org/10.3390/ijgi10080571